CO2 injection for geothermal development associated with EGR and geological storage in depleted high-temperature gas reservoirs. (15th March 2017) - Zhang, Liang; Li, Xin; Zhang, Yin; Cui, Guodong; Tan, Chunyang; Ren, Shaoran
Abstract: High-temperature gas reservoirs (HTGR) come with significant geothermal potentials. Supercritical CO2 has been considered as one of the best heat transmission fluids for geothermal production. In this study, a novel concept technology of CO2 -HTGR system has been proposed to develop the geothermal energy in the depleted high-temperature gas reservoirs through CO2 injection associated with EGR and geological storage. CO2 enhanced gas recovery (EGR) with pressure build-up should be conducted first to establish a CO2 gas reservoir with a low methane content, then the hot CO2 gas in the reservoir is produced for heat utilization and then injected back. Finally, the CO2 gas reservoir is shut down for permanent geological storage. Reservoir numerical simulation has been conducted to study the fundamental processes of this concept technology including the establishment of a CO2 gas reservoir through EGR and pure injection, and the heat mining performance of CO2 gas cycling in the created reservoir. The simulation results indicate that a high injection-production ratio during CO2 EGR can shorten the time of establishing a CO2 gas reservoir. The purity of the established CO2 gas reservoir has a significant influence on the heat mining performance of cyclic CO2 gas. When the CO2 purity in the gas reservoir is higher than 90%, the damage of the remaining methane to the heat mining rate of supercritical CO2 can be controlled within 9.5%. The integrated process of CO2 injection for geothermal development associated with EGR and geological storage is more attractive than the conventional CO2 geothermal system and has a stronger on-site feasibility. Highlights: High-temperature gas reservoirs (HTGR) have huge geothermal potentials. The novel concept of CO2 -HTGR geothermal system has been proposed. CO2 -HTGR geothermal system has excellent heat mining performance. An effective CO2 HTGR can be established through EGR and pressure recovery. The quality of established CO2 HTGR affects the heat mining performance significantly.